Comparison Between the Effect of Silica Fume and Wood Ash Used for the Production of High Performance Mortar (Al-Mansour Journal, 2022)
This paper presents a comparison between the use of silica fume and wood ash for High Performance Mortar (HPM). The different percentages used for each of the silica fume and wood ash are: 6, 8, 10, 12 and 16%. The experimental tests included density, compressive strength and flexural strength. The results illustrate that the use of silica fume increases the density, whereas the wood ash decreases the density of HPM. Besides, the inclusion of Silica fume (10 % as a partial replacement of cement) and wood ash at the same level of replacement gives the best properties of the HPM. In other words, the compressive strength and flexural strength have been enhanced by the inclusion of silica fume and wood ash.
Keywords: High performance mortar; silica fume; wood ash